Pengaruh Akuntabilitas dan Transparansi terhadap Efektivitas Pengelolaan Dana Desa: Kepuasan Masyarakat Desa Waetuo - Andini Dwi Cahyani; Nur Hikmah R; Nurul Azani Misbah; Muh. Ikram S; Nur Fadilah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to examine the effect of accountability and transparency in village fund management on the level of public trust in Waetuo Village, Malangke Barat District, North Luwu Regency. Public trust is one of the most important indicators of the success of village governance, particularly in the management of village finances derived from village funds. Therefore, the application of accountability and transparency. This research uses a quantitative approach with a survey method. The sampling technique applied is proportional random sampling, involving 87 respondents from the Waetuo Village community. Research data were collected through closed-ended questionnaires developed based on indicators of accountability, transparency, and public trust. The collected data were analyzed using multiple linear regression analysis. The results of the analysis show that both partially and simultaneously, accountability and transparency have a positive and significant effect on the level of public trust. This finding indicates that the better the implementation of accountability and transparency in village fund management, the higher the level of public trust in the village government. The coefficient of determination of 36.7% indicates that accountability and transparency variables are able to explain variations in public trust, while the remaining percentage is influenced by other factors outside the research model. These findings confirm that accountability and transparency are essential factors that must be continuously improved to build and maintain public trust in village governan.